TUBERCULOUS ARTHRITIS OF THE ANKLE MIMICKING SYNOVITIS IN CHILD - A CASE REPORT - Erick Yudistira Christanto; Sulis Bayusentono (Journal Orthopaedi and Traumatology Surabaya)
Background: Extrapulmonary Tuberculosis is approximately 10% of all tuberculosis (TB) cases, and the musculoskeletal system's involvement was only 2-4. The incidence of ankle TB was found to be less than 2% of all musculoskeletal TB. The rare occurrence, uncommon site, non-specific symptoms, lack of awareness frequently causes diagnosis difficulties.